Notes on Late Iron Age Celtic peopling in Northern Italy. Settlement dynamics, historical trajectories and cultural features (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
The Celtic peopling south of the Alps represented a multifaceted phenomenon, not much referable to a unitary model. It consists of groups of different origins who settled in differentiated areas, characterized by specifities due to the previous cultural features, which played a crucial role in the emplacement of the newcomers. Moreover, our understanding of Celtic settlement in northern Italy is hampered by a shortage of updated and comprehensive contextual data, above all about settlements.
Keywords: Celts; Cisalpine Gaul; “latenization”; settlement; cultural groups, continuity/discontinuity